Test-retest reliability and agreement of lower-extremity kinematics captured in squatting and jumping preschool children using markerless motion capture technology - Harsted, Steen; Holsgaard-Larsen, Anders; Hestbæk, Lise; Andreasen, Ditte Lundsgaard; Lauridsen, Henrik Hein (Frontiers in Digital Health, 2022)
The clinimetric properties of new technology should be evaluated in relevant populations before its implementation in research or clinical practice. Markerless motion capture is a new digital technology that allows for data collection in young children without some drawbacks commonly encountered with traditional systems. However, important properties, such as test-retest reliability, of this new technology have so far not been investigated. We recorded 63 preschool children using markerless motion capture (The Captury GmbH, Saarbrüken, Germany) while they performed squats and standing broad jumps. A retest session was conducted after one week. Recordings from the test session were processed twice to estimate the software-driven instrumental variability. Recordings from the first and second test sessions were compared to evaluate the week-to-week test-retest reliability. Statistical tests included 95% limits of agreement and intraclass correlations of absolute agreement (ICC). Jump length performance and four kinematic variables demonstrated acceptable instrumental variability (ICC > 0.76). The week-to-week reliability was excellent for jump length performance (ICC = 0.90) but poor to moderate (ICC < 0.55) for the kinematic variables. Our results indicate that preschool children exhibit considerable intra-individual kinematic variation from week-to-week during jump landings and squats. Consequently, we suggest that future work should explore individuals with persistent extreme kinematics over multiple test sessions.